Endotracheal bleed after intra cardiac repair in tetralogy of fallot patients: a diagnostic challenge - Sinha, Lakshmi; Solanki, Hardik J.; Ali, Muzaffar; Agarwal, Saket; Naqvi, Sayyed Ehtesham Hussain; geelani, Muhammad Abid; Datt, Vishnu (International Surgery Journal, 2022)
Background: Tetralogy of Fallot (TOF) is the most common congenital cyanotic heart disease (CCHD) in children. With the development and advancement of paediatric cardiac surgery and intensive care units, a large number of TOF are presenting for cardiac surgery. Operated TOF may suffer from endotracheal (ET) bleeding in postoperative period which results in delayed extubation of patients. ET bleeding is multifactorial with MAPCAs, coagulopathy residual VSD, and high LA pressure being usual causes. The objective of this study was to evaluate those children of TOF who suffered from ET bleeding, their causes and management after intracardiac repair. Methods: This was a single center retrospective study that included patients with a diagnosis of TOF. Total of 27 patients were operated at GB Pant Hospital, Department of CTVS from February 2021 to November 2021. After taking ethical approval we conducted a retrospective study to analyse the cause of endotracheal bleed. Statistical analyses were performed using STATA software version (16.0). Continuous variables were presented as mean±standard deviation (SD) or median (interquartile range [IQR]. Inclusion criteria was- all diagnosed case of tetralogy of fallot patient with age –1.5-8 years, both male and female. Exclusion criteria was- patients having co-morbidities, like juvenile diabetes, hypothyroidism, syndromic patients. Results: Endotracheal bleed noted in majority of patient in those MAPCAs were not coiled, not able to be ligated intaoperatively, they bleed in postoperative period which further delayed extubation of patients. Of the patients with Endotracheal bleed none had a residual cardiac defect. Post-operative mortality was 1/27. Conclusions: We hereby conclude that cause of endotracheal bleed after intracardiac repair of tetralogy of fallot patients can be due to left uncoiled, non- ligated major aorto-pulmonary collateral arteries (MAPCAs).